Pregnancy detection in reindeer (Rangifer tarandus tarandus) - Paul, Elisabeth (2014)
Pregnancy detection during late gestation (last trimester) in domesticated reindeer (Rangifer tarandus tarandus) gives the possibility to select and enclose the pregnant reindeer during calving as protection against predation. The aim of the present study was to compare transrectal ultrasonography and palpation, and also to describe visual examination as traditionally used by herders as pregnancy detection methods in reindeer. In all, 1107 female reindeer were tested for pregnancy with ultrasound in April 2013 and April 2014. 207 from these females were tested with palpation in April 2014. In 2013 ultrasound showed an apparent pregnancy prevalence of 83.1% and a calving rate of 88.3%. In 2014 two tests, ultrasound (US) and palpation (PALP) were conducted independently. Females with an unclear or negative pregnancy result were re-examined by both methods. Observed calving rate was 93.0%. Accuracy for both evaluations was 94.2% (US) and 97.7% (PALP), with sensitivity of 95% (US) and 98.8% (PALP). Both methods showed good results, however palpation was slightly more accurate than ultrasound. Both test outcomes increased to a specificity of 100% and a positive predictive value of 100% when combining the two methods. Hence, combination of both methods and re-examination were found to increase correct test outcomes. Two herders were asked to describe their indicators for visual evaluation of pregnancy. The indicators differed between the herders, but both looked for changes in abdominal and inguinal anatomy. Accuracy was not calculated. However, herders seemed to associate high body weights with pregnancy.